Understanding Oracle Clinical - Johnson, Joan M. (O'Reilly short cut., 2007)
This Short Cut is written to assist you, an Oracle Clinical Developer, with many of the tasks and decisions you may encounter on an occasional basis. These tasks involve study setup and maintenance, account maintenance, handling discrepancies, preparing data sets for analysis, batch-loading data, altering system-level settings and defining standard processes. A working knowledge of screen setup and procedure coding is assumed. Remote Data Capture (RDC), which moves data entry from the CRO or pharmaceutical company to the sites, is fast becoming the preferred way to gather and clean data for.